Hexavalent chromium reduction by Morganella morganii (1Ab1) isolated from tannery effluent contaminated sites of Tamil Nadu, India. (January 2020) - Princy, Selvakumar; Sathish, Sathya Segar; Cibichakravarthy, Balasubramanian; Prabagaran, Solai Ramatchandirane
Abstract: Hexavalent chromium [Cr(VI)] is a toxic pollutant often released from tanneries after treating leather. Due to prolonged exposure to chromium, the niche enables several microorganisms to develop resistance which exhibit high bioremediation prospects. Totally, 126 bacterial strains were isolated from 20 different samples contaminated with tannery effluents collected from various geographical locations of Vellore and Dindigul districts, Tamil Nadu, India. Among them, 52 morphologically diverse isolates were profiled by ARDRA (Amplified Ribosomal DNA Restriction Analysis) into 19 groups. Based on reduction assays eight strains exhibited Cr(VI) resistance at different concentrations (2000–5000 mg/L) under varied growth conditions including pH (5–8) and temperature (25–60 °C). From eight, the strain 1Ab1 identified as Morganella morganii was remarkably distinct which could reduce Cr(VI) at 4600 mg/L in minimal media up to 92%. Reduction on raw tannery effluent sample was also on par up to 90% in 48 h under optimized conditions of pH 7.0 and temperature 37 °C. Subsequently FESEM-EDX and FTIR analysis confirmed the interaction of chromium ions and consequent morphological alterations in the bacterial cell wall. Overall, the strain Morganella morganii (1Ab1) evolved as a potential organism to reduce toxic hexavalent chromium to its non-toxic trivalent form in chromium contaminated systems. Highlights: Bacterial based reduction of toxic Cr(VI) to non-toxic Cr(III). Active role of reductases for metal uptake. Effective alternative for conventional treatment methods. Eco-friendly bioremediation for Cr(VI) removal.